THE INFLUENCE OF LEARNING CREATIVITY ON STUDENT WORK PRODUCTIVITY WITH SELF-EFFICACY AS A MODERATING VARIABLE - Layalil Maghfiroh Zain; Munirul Abidin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of learning creativity on students’ work productivity and examine the moderating role of self-efficacy. The research background highlights increasing demands in both academic and professional environments, which require students to possess not only creativity but also strong self-belief to maintain optimal performance while balancing study and work responsibilities. The study employed a survey method with purposive sampling, involving 100 student workers from various universities. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The findings reveal that self-efficacy has a significant and strong effect on students’ work productivity. In contrast, learning creativity shows no significant effect on work productivity, and self-efficacy does not moderate the relationship between learning creativity and work productivity. These results indicate that self-belief plays a more dominant role than creativity in enhancing students’ productivity. The study provides practical implications for higher education institutions to strengthen students’ self-efficacy development to support both academic and non-academic performance.